Model Komunikasi Internal dalam Pembentukan Kinerja Pegawai Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Tojo Una-Una - Moh. Ilham S. Tawalili; Nurwahida Alimuddin; Samintang Samintang; Sapruddin Sapruddin (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
Communication plays an important role in human life as a tool for social interaction, especially within organizations, where effective internal communication serves as a key factor in achieving goals. This study aims to determine the model of internal communication in improving employee performance at the Regional Library and Archives Office of Tojo Una-Una Regency, as well as the supporting and inhibiting factors. The research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation studies, while data analysis involved reduction, presentation, and conclusion drawing. The results show that the Regional Library and Archives Office applies two types of internal communication: coordinative communication, which is carried out hierarchically, and general (persuasive) communication, which allows the Head of Office to interact directly with staff without bureaucratic channels, particularly for urgent, general, or motivational information. Supporting factors of internal communication include proactive leadership, the use of communication technology, and clear communication channels. Meanwhile, inhibiting factors consist of low employee discipline and inadequate facilities and infrastructure. It is recommended that evaluations and improvements be made in discipline management and the enhancement of work facilities to optimally support the achievement of organizational goals.